Measurement of relative branching fractions of B decays to ψ(2S) and J/ψ mesons. - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (Springer-Verlag, 2012)
The relative rates of B-meson decays into J/ψ and ψ(2S) mesons are measured for the three decay modes in pp collisions recorded with the LHCb detector. The ratios of branching fractions ([Formula: see text]) are measured to be [Formula: see text] where the third uncertainty is from the ratio of the ψ(2S) and J/ψ branching fractions to μ (+) μ (-).